2000
DOI: 10.1046/j.1365-2230.2000.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced acral erythema: report of a case and immunohistochemical findings

Abstract: Chemotherapy-induced acral erythema (CAE) is an uncommon and distinct reaction seen in patients receiving high-dose chemotherapy. The exact pathogenic mechanisms of this disorder are still unknown. We report a 27-year-old woman who presented with red, swollen and painful macules on both palms, clinically consistent with this disease. Histological examination demonstrated vacuolar degeneration of the basal cell layer and spongiotic blisters in the epidermis, especially in the atrophied eccrine ducts and papilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…This occurs partly through the influence of Treg cells on neutrophil survival, as evidenced by a significantly enhanced nuclear hypersegmentation in neutrophils recovered from mice with reduced Treg‐cell numbers. Nuclear hypersegmentation is strongly associated with non‐infectious inflammatory conditions 19–21 and is historically associated with older neutrophils and prolonged survival. More recently, hypersegmented neutrophils resulting from granulocyte colony‐stimulating factor treatment, 22 exhibited increased survival and increased phagocytic and cytolytic capacity 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…This occurs partly through the influence of Treg cells on neutrophil survival, as evidenced by a significantly enhanced nuclear hypersegmentation in neutrophils recovered from mice with reduced Treg‐cell numbers. Nuclear hypersegmentation is strongly associated with non‐infectious inflammatory conditions 19–21 and is historically associated with older neutrophils and prolonged survival. More recently, hypersegmented neutrophils resulting from granulocyte colony‐stimulating factor treatment, 22 exhibited increased survival and increased phagocytic and cytolytic capacity 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Histologic findings of patients in whom biopsies have been performed are generally nonspecific but include changes to the eccrine sweat glands (4,24). Vargas‐Diez et al (24) reported 15 patients who developed acral erythema in response to various chemotherapeutic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Acral erythema has been described as symmetric, painful erythema of the palms and soles with a prodrome of paresthesia and occasional bullous formation with desquamation upon resolution (1). It has been associated with a number of chemotherapeutic agents including 5‐fluorouracil (2,3), cytarabine (4–6), and cyclophosphamide (7). Methotrexate‐induced acral erythema was initially described in 1983 and since then over a dozen reports implicating MTX as the causative agent in the development of acral erythema have been published (8–15).…”
mentioning
confidence: 99%
“…Excretion onto the skin surface may create a microenvironment in which the direct toxic effects of the chemotherapeutic agents may induce the skin lesions 23 . Others have speculated that the accumulation of chemotherapeutic agents within the sweat gland apparatus may trigger an immune response that in turn generates the cutaneous lesions 27 . Unfortunately, the superficial shave biopsy from our patient did not permit analysis of eccrine structures.…”
Section: Discussionmentioning
confidence: 84%